SOCIAL SKILLS AND ACADEMIC BACKGROUND: A COMPARATIVE STUDY AMONG STUDENTS AND PSYCHOLOGY PROFESSIONALS - Diêgo Ferreira de Oliveira; Jackeline Maria de Souza (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The present research had as an objective the comparison of Social Skills (SS) on psychology course undergraduates' and professionals working in the area with at least one year of work performance. Three groups participated in this study: 63 students at the beginning of the course (1st, 2nd and 3rd semesters); 54 students at the end of the course (8th, 9th and 10th semesters); and 25 psychologists. For the data collect it was used a Social Skills Inventory (SSI) that was applied at the university places of work or availability, or via e-mail, with the professionals. The results showed that there were no significant differences in the overall score of Social Skills, neither between the students at the beginning and the end of the course (p=0.319) nor between students at the end of the course and the psychologists (p= 0,70). There was a significant difference in the comparison of students at the beginning of the course and psychologists (p= 0.009). From the manual, it was possible to verify that the majority, of students and professionals, presented a good repertory of SS in its different factors. It was considered still relevant, the development of activities that could enable a major learning of these SS still during graduation, evaluating that they are fundamental to the psychologists' performance. Keywords: Social skills. Psychology. Psychology students. Psychologists.